Protected Graft Copolymer (PGC) in Imaging and Therapy: A Platform for the Delivery of Covalently and Non-Covalently Bound Drugs - Alexei A. Bogdanov Jr, Mary Mazzanti, Gerardo Castillo, Elijah Bolotin (Theranostics, 2012)
Initially developed in 1992 as an MR imaging agent, the family of protected graft copolymers (PGC) is based on a conjugate of polylysine backbone to which methoxypoly(ethylene glycol) (MPEG) chains are covalently linked in a random fasion via N-ε-amino groups. While PGC is relatively simple in terms of its chemcial composition and structure, it has proved to be a versatile platform for in vivo drug delivery. The advantages of poly amino acid backbone grafting include multiple available linking sites for drug and adaptor molecules. The grafting of PEG chains to PGC does not compromise biodegradability and does not result in measurable toxicity or immunogenicity. In fact, the biocompatablility of PGC has resulted in its being one of the few 100% synthetic non-proteinaceous macromolecules that has suceeded in passing the initial safety phase of clinical trials. PGC is capable of long circulation times after injection into the blood stream and as such found use early on as a carrier system for delivery of paramagnetic imaging compounds for angiography. Other PGC types were later developed for use in nuclear medicine and optical imaging applications in vivo. Recent developments in PGC-based drug carrier formulations include the use of zinc as a bridge between the PGC carrier and zinc-binding proteins and re-engineering of the PGC carrier as a covalent amphiphile that is capabe of binding to hydrophobic residues of small proteins and peptides. At present, PGC-based formulations have been developed and tested in various disease models for: 1) MR imaging local blood circulation in stroke, cancer and diabetes; 2) MR and nuclear imaging of blood volume and vascular permeability in inflammation; 3) optical imaging of proteolytic activity in cancer and inflammation; 4) delivery of platinum(II) compounds for treating cancer; 5) delivery of small proteins and peptides for treating diabetes, obesity and myocardial infarction. This review summarizes the experience accumulated by various research groups that chose to use PGC as a drug delivery platform.